MSSR. B's Curio Shop (New York : Thread Waxing Space, 1992)
Anker, Suzanna ; Apfelbaum, Polly ; Bijl, Guillaume ; Bonney, Anney ; Bouillon, Victor ; Coen, Nadia ; Connor, Maureen ; Craven, David ; Durward, Graham ; Dickerson, Paul ; Franklin, Rick ; Gerber, Ava ; Geshlider, Paul ; Hegarty, Laurence ; Ireland, David ; Irons, Shirley ; Jenkins, Michael ; Johnson, Sue ; Lahti, Charles ; Mantje, Aldert ; Masullo, Andrew ; Mitchell, Curtis ; Morgan, Robert ; Morris, Sarah ; Ossorio, Alfonso ; Owens, Catherine ; Pensato, Joyce ; Pondick, Rona ; Rockman, Alexis ; Seator, Glenn ; Seliger, Jonathan ; Sheehan, Maura ; Simard, Claude ; Silverthorne, Jeanne ; Sprethjak, Stephen ; Strik, Berend ; Thek, Paul ; Veneman, Peer ; Vergier, Françoise ; Voss, Ernst ; Walt, Lindsay ; Wiener, Daniel ; Yamamoto, Lynn
MSSR. B's Curio Shop : Thread Waxing Space, New York, June 6 - July 11, 1992
Engels
boek